2012
DOI: 10.1093/ntr/ntr323
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Cigarette Smokers' and Non-Cigarette Smokers' Use of Alternative Tobacco Products

Abstract: More information on adolescent use of alternative tobacco products is needed. Current cigarette use declined 3.4% annually over 2004-2009 for the NYTS 14- to 17-year-old population, but this cohort's use of alternative tobacco products was unchanged. The number of adolescents aged 14-17 who did not smoke cigarettes but used alternative tobacco products increased 5.9% per year over the same period. Current surveillance measures need to be expanded in order to gain a more comprehensive understanding of adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Our findings show that the odds of using e-cigarettes in the past 30 days are more than four times greater for hookah users, while the odds of using cigarettes in the past 30 days are more than five times greater among hookah users. This is not surprising, as previous analysis of data from the NYTS found that use of one alternative tobacco product is a risk factor for using another, among cigarettes smokers and non-cigarette smokers 27 . Odds ratios for use of various alternative tobacco products as a risk factor for using another type of alternative tobacco product varied from 1.52 (95% CI 1.12, 2.07) to 60.97 (95% CI 31.38, 118.45) among respondents 27 .…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Our findings show that the odds of using e-cigarettes in the past 30 days are more than four times greater for hookah users, while the odds of using cigarettes in the past 30 days are more than five times greater among hookah users. This is not surprising, as previous analysis of data from the NYTS found that use of one alternative tobacco product is a risk factor for using another, among cigarettes smokers and non-cigarette smokers 27 . Odds ratios for use of various alternative tobacco products as a risk factor for using another type of alternative tobacco product varied from 1.52 (95% CI 1.12, 2.07) to 60.97 (95% CI 31.38, 118.45) among respondents 27 .…”
Section: Discussionmentioning
confidence: 59%
“…This is not surprising, as previous analysis of data from the NYTS found that use of one alternative tobacco product is a risk factor for using another, among cigarettes smokers and non-cigarette smokers 27 . Odds ratios for use of various alternative tobacco products as a risk factor for using another type of alternative tobacco product varied from 1.52 (95% CI 1.12, 2.07) to 60.97 (95% CI 31.38, 118.45) among respondents 27 . Additionally, studies associate e-cigarette use with increased intention to smoke cigarettes, openness to trying cigarettes, and the actual initiation of cigarette smoking [31][32][33] .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…5,6 A recent report from the Centers for Disease Control and Prevention warns that the drop in cigarette consumption is being "offset by increases in other forms of tobacco." 7 Although alternative tobacco use may have originated among immigrants from South Asia and the Middle East, use of hookah has clearly moved into the mainstream US population.…”
mentioning
confidence: 99%